Pengembangan Spiritualitas dalam Pendidikan dan Pelatihan Berbasis Gender dalam Perspektif Islam - Masfifah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This paper discusses the development of spirituality in education and training based on gender in Islamic perspective. The discussion included an understanding of the discourse of gender equality in Islamic perspective, and the development of spirituality in education and training based on gender in Islam. The conclusions in this study show that, the existence of women in Islamic perspective is equal to men in terms of brotherhood, affection, help in the fields of education, social, economic and political activities. However, because the structure and physical and biological characteristics of men and women are different, their functions are naturally also naturally different. Therefore, it is very unfair if in all areas of life, women must be equal with men and vice versa. In education and training, spiritual attitudes can be integrated into any theme or concept that will be studied with participants in education and training. Educational and training materials in the form of theories, concepts, facts, and research findings are associated with the holy book (al-Qur'an) and al-Hadist so that it can raise awareness that there is a knowing, omnipotent thing over everything so that it will eventually foster faith and devotion for Allah SWT.